Tingkat Efektifitas Digitalisasi pada Pelayanan Administrasi di Kantor Kecamatan Medan Amplas - Rozali Ilham; Abdhel Hasbi Skd (Pusat Riset dan Inovasi Nasional, 2025)
The rapid development of information technology has accelerated the transformation of public services in Indonesia toward digitalization. This study aims to analyze the effectiveness level of digitalization in administrative services at the Medan Amplas District Office. A qualitative approach was used, employing a literature review method by collecting data from books, scientific journals, policy documents, and institutional performance reports. The results show that the digitalization of administrative services in Medan Amplas District has improved service timeliness, cost and procedure transparency, and public satisfaction, with system adoption rates increasing from 30% to 65% between 2018 and 2022. Digitalization has also provided benefits in terms of time and cost efficiency, as well as enhanced staff productivity. However, several challenges remain, such as infrastructure limitations, uneven digital competencies among staff, regulatory inconsistencies, and organizational culture resistance to change. In conclusion, the digitalization of administrative services at Medan Amplas District has been effective but still requires continuous improvement in technical aspects, human resource capacity building, regulatory harmonization, and cultural change to achieve sustainable optimization of public services.